Minat Masyarakat Kota Mataram Berwakaf Uang: Sikap Sebagai Variabel Mediasi - Hidayat, Ali Akbar; Huzaini, Moh.; Husni, Vici Handalusia; Hak, Muhamad Bai'ul; Fadlli, Muhammad Dzul (Institut Agama Islam Negeri Madura, 2024)
This study aims to analyze the factors influencing the interest of society to cash waqf in Mataram City. This research uses a quantitative approach. The population of this study is unknown, so sampling uses a purposive sampling. The number of samples was 100 respondents taken based on the Lemeshow formula. The data used is primary data from the questionnaires. This study uses data analysis with the Structure Equation Model-Partial Least Square (SEM-PLS). The results showed that subjective norms have a positive but insignificant effect on the attitude to cash waqf. Religiosity and knowledge have a positive and significant effect on the attitude to cash waqf. Subjective norms and knowledge have a positive and significant effect on the interest in cash waqf. Religiosity and attitude have a positive but insignificant effect on interest in cash waqf. Subjective norms, religiosity and knowledge have a positive but insignificant effect on interest in cash waqf mediated by attitudes. The Adjusted R-Square value is 0.513 or 51.3 per cent, meaning that the variables of subjective norms, religiosity, knowledge and attitudes are able to explain the variation in the variable interest in waqf money by 51.3 percent which is classified as a moderate model.